Subjective Beliefs About Trust and Reciprocity Activate an Expected Reward Signal in the Ventral Striatum - Fairley, Kim; Vyrastekova, Jana; Weitzel, Utz; Sanfey, Alan G. (Frontiers in Neuroscience, 2019)
There is overwhelming evidence that the evaluation of both reward decisions and their associated outcomes are closely linked with bilateral activation of the ventral striatum, with these insights stemming from tasks such as the Monetary Incentive Delay task for lotteries and multiround Trust Games for social settings. The essential element in these tasks is an externally-provided cue associated with specific gains/trustworthy partners and losses/non-trustworthy partners. However, in reality people typically use their own beliefs to guide their decision-making and assess the likelihood of positive or and negative outcomes. As when participants assess the relationship between cues and rewards, individuals should anticipate rewards in correspondence to their beliefs, i.e. the higher the belief of obtaining a reward in the future, the higher the anticipation of reward. In this study, we use decision-makers’ own, naturally-occurring, beliefs about both social and nonsocial contexts to examine the subsequent outcome of their choices. We hypothesize that mechanisms of belief-mediated reward processing are mediated by neural activation in the ventral striatum. An essential feature of our design is the elicitation of individuals’ beliefs prior to the decision-making task itself. Furthermore, our incentivized, non-deceptive, decision-making task distinguishes between social – implemented by a Trust Game –¬ and non-social sources, as well as risk and ambiguity as underlying types of uncertainty. Our main result shows that individual beliefs regarding reciprocity likelihoods in both the Trust Game and the lottery influence the amount invested. Subsequently, only the investment amount in the Trust Game parametrically modulates anticipatory reward and outcome evaluation in the ventral striatum. This study demonstrates a first approach at using participants’ subjective sets of beliefs to examine reward processing. We discuss its potential promise, outline some limitations, and propose follow-up studies to extend the current approach.